De mineur à expert environnemental - Sylvain Le Berre; Sophie Bretesché (Revue d'anthropologie des connaissances)
In France, uranium mining was carried out for half a century (1948-2001), a time span marked by considerable transformations in the training and in the professional vision of miners. This article analyses the transformations of vision, gestures and practices of the workers: starting with the peasant miners, it describes the changes produced by the introduction of machines and by the exploitation of open-pit mines until the reconversion in the 1990s of the last teams into environmental experts. While stating that the professional vision of uranium miners is not limited to an optical dimension, but mobilizes all the senses, the analysis focuses on the perceptions and attention of workers and on their various contextual configurations (attention to oneself, to others, to external dangers).